The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/01945998211010443
|View full text |Cite
|
Sign up to set email alerts
|

Association Between 5‐Item Modified Frailty Index and Short‐term Outcomes in Complex Head and Neck Surgery

Abstract: Objectives To evaluate the impact of preoperative frailty on short-term outcomes following complex head and neck surgeries (HNSs). Study Design Cross-sectional database analysis. Setting American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database. Methods The 2005 to 2017 ACS-NSQIP was queried for patients undergoing complex HNS. Five-item modified frailty index (mFI) was calculated based on functional status and history of diabetes, chronic obstructive pulmonary disease, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 49 publications
2
38
1
Order By: Relevance
“…The positive association between patients' mFI‐5 scores and increases in hospital LOS has previously been reported after vestibular schwannoma resection, 15 head and neck microvascular reconstruction, 13 thyroidectomy, 11 and complex head and neck surgery. 12 In each of these studies, the mFI‐5 score has been shown to be a better predictor for postoperative complications than patient age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive association between patients' mFI‐5 scores and increases in hospital LOS has previously been reported after vestibular schwannoma resection, 15 head and neck microvascular reconstruction, 13 thyroidectomy, 11 and complex head and neck surgery. 12 In each of these studies, the mFI‐5 score has been shown to be a better predictor for postoperative complications than patient age.…”
Section: Discussionmentioning
confidence: 99%
“…The mFI‐5 has been shown to be predictive of post‐operative complications. 10 It has been used to study complications in settings including thyroidectomy for multinodular goiter, 11 short‐term surgical outcomes following complex head and neck surgery, 12 perioperative risk in head and neck microvascular reconstruction, 13 and postoperative complications after skull base surgery. 14 The objective of this study was to assess the rate of complications after middle fossa craniotomy for repair of spontaneous CSF leak or encephalocele and evaluate the ability of the mFI‐5 to predict the risk of increased length of stay or added morbidity after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…It consists of four comorbid conditions (pulmonary disease, congestive heart failure, diabetes mellitus and hypertension) and one functional status (16-18). Similar to the original 11-mFI, the 5-mFI has been proven to be an acceptable predictor of outcome in various surgeries, including paraesophageal hernia repair, multiorgan resections, trauma, nephrectomy, breast reconstruction, spine surgery, and complex head and neck surgery (15,16,(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 89%
“…The RAI is a validated widely used model to predict frailty and short‐term adverse events in oncology patients (Hall et al, 2017). The mFI 5 is a validated risk index to predict postoperative adverse events in head and neck patients (Goshtasbi et al, 2021; Subramaniam et al, 2018; Wachal et al, 2017). Tumor‐related factors, including AJCC eighth Edition TNM stage, subsite, histopathology and need for adjuvant treatment were also documented.…”
Section: Methodsmentioning
confidence: 99%